A compreensão da construção de conhecimentos físicos por meio de um aplicativo para smartphones e tablets no ensino de física em uma universidade pública no estado do Rio Grande do Sul - Silva, Luciano Racts Claudio da (2018)
The utilization of DT (Digital Technologies) in educational institutions is no longer an alternative, becoming a necessity, given the context of cyberculture in which we are inserted. However, the context of schools is still lacking in the provision of devices and artifacts to carry out activities involving the use of technologies. Therefore, an alternative is to use devices owned by students, such as smartphones and tablets. This research sought to investigate the contribution of the use of an app, available for smartphones and tablets, in studies in the discipline of Fundamentals of Physics of a public university in the discipline of Fundamentals of Physics of a public university in the State of Rio Grande do Sul. The research had a qualitative character, of case-study type and the methodology of analysis used was the Discursive Textual Analysis – ATD. The results showed that the use of devices, such as smartphones and tablets, can bring the practice closer to theory, helping to build students knowledge. These resources can help the teach work, but there is a need for pedagogical planning to define its use. The teacher nedds to consider, more and more, the integration of digital technologies with his pedagogical proposal. The results found in this research motivate to give segment the use of smartphones and tablets and, at the same time, to recommend the need to offer elements for the qualification of teachers, in order to help potentialize the use of technologies in teaching pratices.